Socioeconomic Dimensions of Education in Islamic Education - Holilur Rahman; Fathul Rahman; Ach.Sudaryo; Abdul Hannan (STIT Attaqwa, 2025)
This study discusses the relationship between socio-economic dimensions and Islamic education with a focus on its influence on societal development. Through in-depth analysis, this research aims to reveal how socio-economic factors influence accessibility, distribution of resources, and the role of religious institutions in Islamic education. With an interdisciplinary approach, this study highlights the importance of socio-economic integration in Islamic religious education to create a more inclusive and sustainable society. The results of this research are expected to provide an important contribution to the development of Islamic education policies that are more holistic and effective in the socio-economic context of society. Thus, this study offers a comprehensive view of how the socio-economic dimension plays a crucial role in the development of Islamic education for a better future